The Effectiveness of A Cognitive Behavioral Guidance Program To Develop The Need For Beauty Among Middle School Female Students (Journal of the College of Basic Education, 2025)
The current study aims to identify the effectiveness of a cognitive behavioral guidance program to develop the need for beauty among middle school female students. To achieve this goal, the following hypotheses were verified:There are no statistically significant differences at a significance level of (0.05) between the mean scores of the experimental group in the pre- and post-tests on the Need for Beauty Scale.2There are no statistically significant differences at the significance level (0.05) between the average scores of the experimental and control groups in the post-test on the Need for Beauty Scale.The cognitive behavioral guidance program is not effective in developing the need for beauty among middle school female students.The current research is limited to female students of the preparatory stage in the fourth and fifth grades of preparatory school in Al-Khalis schools affiliated with the General Directorate of Education in Diyala, for the academic year (2024-2025) morning study, and in order to achieve the goal of the research and its hypotheses, the researcher used the quasi-experimental design (design of the experimental and control groups with a pre- and post-test), and she built a scale of the need for beauty based on the theory (Maslow) where the number of paragraphs reached (21) paragraphs.The sample of the application was chosen intentionally from two schools with (10) female students for the experimental group and (10) female students for the control group. The sample of the statistical analysis consisted of (400) female students, then they were chosen intentionally from Al-Khalis schools affiliated with the General Directorate of Education in Diyala for the academic year (2024-2025). Then the researcher designed the cognitive behavioral guidance program according to the “Mickenbaum” theory to develop the need for beauty according to the Borders and Drury model. The researcher used the Statistical Package for Specific Purposes (SPSS) to analyze the research data. She reached the following results:There was a statistically significant difference between the students on the Need for Beauty scale in the pre- and post-tests.There was a statistically significant difference between the average ranks of the experimental group students and the average ranks of the control group students in the post-test.3.The effectiveness of the cognitive behavioral guidance program in developing the need for beauty among middle school female students was (0.628(.In light of the results of the current study, the researcher developed a set of recommendations and proposals, some of which are mentioned below:A- RecommendationsThe Need for Beauty Scale, which was prepared by the researcher, can be used by researchers and counselors to identify female students with a low need for beauty.The possibility of utilizing the guidance program and its approved techniques and activities to develop other behaviors among female students in the intermediate and preparatory stages.B - SuggestionsUsing other methods and techniques to develop the need for beauty through conducting an experimental study, such as(reality therapy, positive reinforcement, creativity, and art).Conducting similar studies on other samples of female students at different educational levels, such as university or intermediate, to verify the effectiveness of the cognitive behavioral guidance program in developing the need for beauty.